The comparison and relationship of IHSG, NIKKEI, and NASDAQ - Gracia H. Mamesah; Kristianto Harikatan; Lidya C. M. Hutapea; Marchanda C. Palalangan (Yayasan Widyantara Nawasena Raharja, 2022)
The movement of market indices in Indonesia, Japan and the United States tends to be uncertain during the COVID-19 pandemic. This study aims to examine the relationship between the three markets and compare performance during the pandemic. The samples used are the IHSG, NIKKEI, and NASDAQ with an observation period from 19 November 2021 to 31 May 2022. This study finds that during the observed period the market return of the IHSG still has a positive performance compared to NIKKEI and NASDAQ. However, the mean difference test also proves that the performance gap between the markets of the three countries is still relatively the same. In addition, this study also shows that there is a unidirectional relationship between IHSG, NIKKEI, and NASDAQ.